Rescuing the Brazilian Agave breeding program: morphophysiological and molecular characterization of a new germplasm - Raya, Fabio Trigo; de Carvalho, Lucas Miguel; José, Juliana; da Cruz, Larissa Prado; Almeida, Rafael Leonardo; Delevatti, Heliur Alves de Almeida; Silveira, Neidiquele Maria; da Silva, Simone Ferreira; Pissolato, Maria Dolores; de Oliveira, Adriele Bárbara; dos Reis, Wagner José Villela; de Abreu, Luís Guilherme Furlan; et al. (Frontiers in Chemical Engineering, 2023)
Agaves have been a valuable resource in dryland areas for centuries, providing fibers (sisal), food, and beverages. However, the advent of synthetic fibers has led to a decrease in research on Agave, resulting in the cessation of breeding programs in Brazil. With the rise of climate change, there is renewed interest in Agave for its potential as a biofuel feedstock in semiarid regions. Since 2016, we have been collecting Agave accessions throughout the country and retrieving what is left of Brazil's original breeding program to establish a new germplasm bank. Here, we evaluated 21 of those accessions growing in the field. We used molecular markers and morphophysiological traits to characterize the plants. Based on the Mayahuelin molecular marker, we were able to reconstruct a phylogeny for the Brazilian accessions. The morphophysiological traits explained 34.6% of the phenotypic variation in the dataset, with physiological traits such as leaf water content, effective quantum efficiency of photosystem II (ΦPSII), and specific leaf mass (SLM) as the most significant traits. Specifically, we evaluated nine Agave species and found that the physiological traits, rather than the morphological ones, were the most significant. Leaf water content was negatively correlated with SLM, which could be used as a marker for selecting cultivars with higher biomass accumulation. Interestingly, ΦPSII and 2 This is a provisional file, not the final typeset article chlorophyll content were negatively correlated, suggesting photochemical adaptations throughout the rosette. Molecular and phenotypic data suggest that A. amaniensis, which is frequently considered a synonym of A. sisalana, is effectively another species. Overall, this study provides valuable information on the physiological traits of Brazilian Agave accessions and is a starting point for selecting more productive and climate-resilient cultivars for biorenewables production.